1999
DOI: 10.1074/jbc.274.23.16370
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel SNF2/SWI2 Protein Family Member, SRCAP, Which Interacts with CREB-binding Protein

Abstract: The ability of cAMP response-element binding protein (CREB)-binding protein (CBP) to function as a co-activator for a number of transcription factors appears to be mediated by its ability to act as a histone acetyltransferase and through its interaction with a number of other proteins (general transcription factors, histone acetyltransferases, and other co-activators). Here we report that CBP also interacts with a novel ATPase termed Snf2-Related CBP Activator Protein (SRCAP). Consistent with this activity, SR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
106
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(113 citation statements)
references
References 34 publications
6
106
0
1
Order By: Relevance
“…In summary, previous to this work it was known that in transient transfection assays SRCAP functions to activate transcription (17,18), and in vitro studies in our laboratory indicated that it catalyzes incorporation of H2A.Z into nucleosomes (16). The current work completes the picture as to how SRCAP may regulate transcription.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In summary, previous to this work it was known that in transient transfection assays SRCAP functions to activate transcription (17,18), and in vitro studies in our laboratory indicated that it catalyzes incorporation of H2A.Z into nucleosomes (16). The current work completes the picture as to how SRCAP may regulate transcription.…”
Section: Discussionsupporting
confidence: 59%
“…It is not clear, however, whether the decreased transcription observed results solely from the loss of H2A.Z incorporation or whether the loss of other SRCAP activities is a contributor. This latter possibility is suggested by our studies indicating that SRCAP contains several additional domains capable of activating transcription independent of the histone exchange reaction (17,18).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Four of the proteins identified by mass spectrometry belong to the SWI/SNF family of proteins and include the BRG1-associated factor (BAF) 170, BAF 155, BAF 47/INI1, and the SWI/SNF-related CBP activator protein (SRCAP) (40). BAF 170 and BAF 155 are highly similar homolog of the yeast SWI3 protein, whereas BAF 47/INI1 represents the mammalian homolog of the yeast SNF5 protein.…”
Section: Resultsmentioning
confidence: 99%
“…29 We have also shown that p400 is able to directly interact with the ERα, which could be responsible for the recruitment of the complex to ERα target genes, and subsequent H2A.Z incorporation. 30 Furthermore, a similar scenario could be possible for SRCAPmediated incorporation of H2A.Z since it interacts with the CREB-binding protein (CBP) co-activator, 48 which in turn interacts with several transcriptional activators. 49,50 Additionally, another study has shown a strong correlation between the presence of Myc and that of H2A.Z to promoter regions.…”
Section: Histone H2azmentioning
confidence: 99%